Enterococcus in routinary microbiology work - Guevara D., José (1997)
In the last years, importance of Enterococcus has been increasing because it is now known as causal agent of difficult-to-treat nosocomial infections, mainly due to their antimicrobial resistance. We identified Enterococcus strains using selective media to isolate it, differential assays for strains identification, and standarized disk-diffussion methods to assess antimicrobial susceptibility. Between march and november 1996, 113 strains of Enterococcus were isolated, 65,4% of which come from vaginal discharges, and the remainder from seminal fluid, urine specimens, faringeal secretions, ascitid fluid, sputum, skin wounds samples, prostatic fluid and uretral fluid. E. faecalis give a total of 88,5% of isolates, followed by E. faeccium, E. pseudoavium, E. avium, E. durans y E. raffinosus. Antibiogram analysis using 13 antimicrobial single drugs and another 2 combined with betalactamase-inhibitors, showed that 97,3% of Enterococcus were ampicillin-sensitive. We concluded that isolated Enterococcus strains show, up to now, a small resistance to ampicillin.